Attachment and inter-individual differences in empathy, compassion, and theory of mind abilities - Gallistl, Mathilde; Kungl, Melanie; Gabler, Sandra; Kanske, Philipp; Vrticka, Pascal; Engert, Veronika (Attachment and Human Development, 2024)
Social processing, namely the ability to understand others’ cognitive and affective states, is crucial for successful social interaction. It encompasses socio-affective abilities such as empathy and compassion, as well as socio-cognitive abilities such as theory of mind (ToM). This study examined the link between social processing and attachment. Our study goes beyond previous research in that social processing abilities were assessed in a single, state-of-the-art behavioral paradigm using video narratives, the EmpaToM. Attachment was captured with the Adult Attachment Interview (N = 85; 50.60% women, Mage = 25.87 ± 4.50 years) measuring participants’ present-day capacity to think about and communicate attachment-relevant information about the past. Additionally, a self-report attachment questionnaire was employed (N = 158). We found that AAI-based attachment security (vs. insecurity) was associated with higher behavioral ToM abilities. Furthermore, self-reported attachment avoidance was negatively correlated with behavioral compassion abilities. Our findings provide further evidence that interview-based and self-reported attachment measures do not converge, but may rather be understood as capturing different facets of attachment that relate to different components of social processing. We conclude that individuals with secure, non-avoidant attachment show social abilities that allow them to better understand others’ thoughts and generate positive, caring emotions in face of others’ distress.
CRIS-Team Scopus Importer:2024-08-02
Keywords: adult attachment interview; Attachment; compassion; empathy; theory of mind